2021
DOI: 10.3390/healthcare9060704
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Prescription Medication in an Internal Medicine Ward

Abstract: Aging-related loss of resilience associated with the lack of evidence regarding the therapeutic efficacy of medicines can prompt a lack of efficacy of treatments and multiple prescriptions. This work aims to characterize the medication profile of Portuguese older adult inpatients and explore the relationship between hospitalization days and the consumption of medicines. A retrospective data analysis study in older patients who were admitted to a medical internal medicine ward during 2019. The median age of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…A total of 3873 diagnoses were registered, 21.4% belonging to the group of diseases related to the circulatory system, 6.4% to endocrine, nutritional, and metabolic diseases, and 10.7% to respiratory system diseases. A detailed characterization of the included population can be found in a previous study [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 3873 diagnoses were registered, 21.4% belonging to the group of diseases related to the circulatory system, 6.4% to endocrine, nutritional, and metabolic diseases, and 10.7% to respiratory system diseases. A detailed characterization of the included population can be found in a previous study [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Considering the need for deprescribing to reduce polypharmacy [ 33 ], it becomes important to reduce the number of prescribed medicines, especially if PIM prescriptions occur [ 19 , 34 ]. However, as previously described, the multiple comorbidities of internal medicine inpatients associated with the lack of evidence for the use of some medicines in older adults and the need to treat/stabilize the cause of the hospitalization favors the prescription of multiple drugs, including PIMs [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that 64% of liver [ 4 ] and 63% of kidney transplant recipients use NSAIDs and/or analgesics [ 4 , 5 ]. In contrast, analgesics and antipyretics were recorded only in 6.6% of patients hospitalized in the internal medicine wards [ 21 ]. Such cohort-related discrepancies may be explained by the differences in the indications, population-specific comorbidities, pain burden and medical advice, age, drug education, patients’ beliefs and study methodologies.…”
Section: Discussionmentioning
confidence: 99%
“…People with intellectual disabilities were more likely than those in the general population cohort to be prescribed paracetamol for all investigated types of pain, and were less likely to have a prescription for NSAIDs [ 20 ]. Paracetamol was also the most frequent among analgesics and antipyretics recorded in patients hospitalized in the internal medicine ward [ 21 ]. We hypothesize, that CKD patients pay more attention to their kidney function and are better educated about NSAIDs nephrotoxicity.…”
Section: Discussionmentioning
confidence: 99%